TO INVESTIGATE THE EFFECT OF HEAT TREATMENT ON FRACTURE TOUGHNESS OF WELDED JOINTS - Hameed, A.; Pasha, R. A.; Khan, A. R.; Khan, M. Z.; Shah, M. (The Nucleus, 2013)
Annealing as a post weld heat treatment (PWHT), increases toughness in the welding joints of medium carbon steel in the same way as it increases toughness of the non-welded medium carbon steel. Measurement of increase in toughness through PWHT is focus of the present research work. Welded samples of commercially available steel AISI1035 have been used for the proposed evaluation. The samples welded by two different techniques namely oxyacetylene gas welding and manual metal arc welding, passed through annealing process along with non-welded samples for comparison of increase in toughness. Toughness measured by impact tests revealed the improvement, which in the order of increasing effects is in gas welded, electric welded and non-welded samples. The aim of the present research was to measure the improvement in fracture toughness through post weld heat treatment (annealing). It has been shown that toughness increases as the structural flaws decrease.